Age-dependent effects of H2S on post-traumatic stress disorder in adolescent and adult mice - Gu, Bing; Li, Ting; Zhao, Haifen; Yue, Rui; Luo, Qian; Yu, Shuwen; Li, Tingting; Zhao, Yijing; Liu, Dexiang; Wang, Zhen; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2025)
BackgroundAmong people with post-traumatic stress disorder (PTSD), there is an increased prevalence of age-related diseases. However, the biological mechanisms underlying this phenomenon remain incompletely understood.MethodsThe expression of cystathionine β-synthase (CBS), one of the main enzymes for endogenous hydrogen sulfide (H2S) production in the brain, is age-dependent. In this study, we examined the influence of CBS/H2S on anxiety and depression-like behavior following the inescapable foot shock (IFS) procedure during early adolescence (postnatal days 28-35) or adulthood (postnatal days 63-70).ResultsOur results showed that adult PTSD mice exhibited more pronounced decreases in H2S content and CBS expression in the hippocampus, which were associated with anxiety and depression-like behavior compared with adolescent PTSD mice. Administration of exogenous H2S significantly improved anxiety and depression-like behavior, mitigated synaptic plasticity deficits, and activated the CREB/BDNF signaling pathway in the hippocampus of adolescent PTSD mice. In addition, we found that high dose H2S could improve anxiety and depression-like behavior, mitigate synaptic plasticity deficits, and activate the CREB/BDNF signaling pathway, as well as increase H2S levels in the hippocampus. In contrast, injection of CBS antibody in the hippocampus of adult mice increased anxiety and depressive-like behavior. ConclusionThese results suggest that CBS/ H2S modulates PTSD-like behaviors in an age-dependent manner and may promote synaptic plasticity through activation of the CREB/BDNF pathway in the hippocampus of mice after IFS exposure.